Herpes Zoster and COVID-19 Vaccination: A Narrative Review - Potestio L; Megna M; Villani A; Cacciapuoti S; Scalvenzi M; Martora F (Dove Medical Press, 2023)
Luca Potestio, Matteo Megna, Alessia Villani, Sara Cacciapuoti, Massimiliano Scalvenzi, Fabrizio Martora Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, ItalyCorrespondence: Luca Potestio, Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Via Pansini 5, Napoli, 80131, Italy, Tel +39 - 081 - 7462457, Fax +39 - 081 - 7462442, Email potestioluca@gmail.comAbstract: COVID-19 was a worldwide emergency, leading to a global health crisis, which completely revolutionized every aspect of human life. Several strategies were adopted to limit the spreading of the infection such as testing and contact tracing, quarantine and isolation, use of face mask, social distancing, lockdowns, travel restrictions, etc. Of these, vaccines were the most important measures to reduce the transmission of the virus and the severity of the infection, in order to overcome the pandemic. Fortunately, vaccination campaign was a success, showing to be efficient in controlling and preventing the COVID-19, reducing the risk of disease progression, hospitalization, and mortality. Monitoring and addressing vaccine-related adverse events have been essential for maintaining public confidence. Indeed, with the increasing number of vaccines administered, various cutaneous reactions have been reported, making dermatologists key players in their recognition and treatment. Particularly, several cutaneous diseases and cutaneous findings have been reported. Of note, also viral reactivations have been described following COVID-19 vaccination. Among these, varicella zoster virus (VZV) reactivation has been collected. Globally, an early diagnosis and an accurate treatment of herpes zoster (HZ) is mandatory to reduce possible complications. In this context, we conducted a review of the current literature investigating cases HZ following COVID-19 vaccination with the aim of understanding the possible causal correlation and underlying pathogenetic mechanisms to offer clinicians a wide perspective on VZV reactivation and COVID-19 vaccines.Keywords: COVID-19, vaccination, herpes zoster, safety